Diversity beliefs are associated with orientations to teaching for diversity and social justice: A study among German and Finnish student teachers. (March 2023) - Rissanen, Inkeri; Kuusisto, Elina; Timm, Susanne; Kaukko, Mervi
Abstract: This mixed methods study explored German ( n  = 477) and Finnish ( n  = 379) student teachers' color-blind, multiculturalist, and polyculturalist diversity beliefs. Statistical analyses identified polyculturalism and multiculturalism as the most prominent diversity beliefs among the student teachers and detected associations between diversity belief profiles and student teachers' orientations to teaching for diversity and social justice. Polyculturalism, in particular, emerged as significant predictor of student teachers' orientations to teaching for diversity and social justice. Qualitative analysis of responses to open-ended questions revealed that polyculturalism was internalized by the student teachers superficially. The implications of the findings for further research and teacher education are discussed. Highlights: Statistical analyses identified polyculturalism and multiculturalism as the most prominent diversity beliefs. Polyculturalism was strongly associated with student teachers' orientations to teaching for diversity and social justice. Qualitative data revealed a weaker degree of polyculturalism than did quantitative measures. Developing approaches to strengthen polyculturalist diversity beliefs in intercultural teacher education is recommended.